Implikasi Kafaah terhadap Maraknya Pernikahan Dini - Muhammad Zainuddin Sunarto; Mohamad Syariful Umam (PALAPA, 2023)
Marriage with teenagers under the age of 20 who are not ready to marry is known as "early marriage." Early marriage is seen as a way for teenagers to avoid sins, namely free sex, but there are also those who do it outside of marriage and become pregnant outside of marriage. This often happens in society. Therefore, Islam recommends kafaah in marriage in order to form a family that is sakinah mawaddah warahmah. Because it has a positive impact on the course of marriage, kafaah is considered a topic that must be considered when choosing a partner. Through the concept of kafaah, one can make balanced choices for oneself, allowing families to feel compatible with one another. This type of research uses a sociological approach in the field. The primary data source for this research is field data, which includes the results of interviews and observations. Meanwhile, secondary data sources were obtained from journal articles, theses, hadiths, and the Koran. The purpose of this study was to determine the effect of kafa'ah on the frequency of early marriage. Based on the findings of this study, there are several internal and external factors that encourage youth in Karang Melok Village to marry young. Internal factors include the need for love to meet one's needs. while external factors such as the existence of peers influence the implementation of marriage.